The impact of FDI quality characteristics on carbon emission intensity: Evidence from China - Ma, Wenjing; Liu, Kai; Li, Yunlong; Zhang, Huarong (Frontiers in Environmental Science, 2022)
Using data from 30 provincial-level in China, this paper investigates the impact of FDI quality characteristics on carbon emission intensity. Based on the Copeland-Taylor model, the mechanism of the impact of FDI quality characteristics on carbon emission intensity is also investigated. The key findings demonstrate that FDI quality traits considerably lower regional carbon intensity, and the result is still robust after considering the spatial correlation and using IV-2sls in consideration of endogeneity. the FDI quality characteristics mainly reduce carbon emission intensity through green technology improvement, industrial structure, and factor endowment structure optimization. Moreover, Further evidence shows that there are heterogeneous effects with regards to regional and FDI quality characteristics. From the standpoint of FDI quality characteristics, this study adds to the literature on FDI and environmental pollution. Policy recommendations for China are also discussed in this paper, which can serve as a guide for other emerging nations.